The Meaning of Covid-19 Social Assistance For The New Poor in Kedunglegok Village, Purbalingga, Central Java: Makna Bantuan Sosial Covid-19 Bagi Masyarakat Miskin Baru di Desa Kedunglegok, Purbalingga, Jawa Tengah - Anif Muchlashin; Krisdyatmiko (Fakultas Ilmu Sosial dan Ilmu Politik, 2022)
ABSTRACT: The spread of Corona Virus Diseases 2019 or better known as Covid-19 is expanding every day. The public in general is faced with health-related anxiety that threatens them, but for the poor, the concern is not only about health but also economic conditions to survive in the midst of the Covid-19 pandemic. The existence of vulnerable communities who become the new poor is also a problem in itself. Social assistance for communities affected by the Covid-19 pandemic is very important to survive in the midst of the Covid-19 pandemic. The existence of social assistance serves to provide assistance to the poor in the midst of a very tense situation. Regarding the meaning of Covid-19 social assistance and how the condition of the poor recently affected in Kedunglegok Village in providing views on social assistance became the main focus of the researcher's questions. ABSTRAK: Persebaran Corona Virus Diseases 2019 atau yang lebih dikenal dengan Covid-19 semakin meluas setiap harinya. Masyarakat pada umumnya dihadapkan dengan keresahan terkait kesehatan yang mengancam dirinya, namun bagi masyarakat miskin yang diresahkan bukan hanya soal kesehatan melainkan kondisi ekonomi untuk tetap bertahan hidup di tengah pandemi Covid-19. Adanya masyarakat rentan yang menjadi masyarakat miskin baru juga menjadi permasalahan tersendiri. Bantuan sosial bagi kalangan masyarakat terdampak pandemi Covid-19 merupakan hal yang sangat penting untuk survive di tengah pandemi Covid-19. Keberadaan bantuan sosial berfungsi untuk memberikan pertolongan pada masyarakat miskin di tengah situasi yang sangat mencekam. Terkait dengan bagaimana makna bantuan sosial Covid-19 dan bagaimana keadaan masyarakat miskin baru terdampak di Desa Kedunglegok dalam memberikan pandangan terhadap bantuan sosial menjadi sorotan utama pertanyaan peneliti.